THE STATE OF THE REGULATORY BASE FOR THE PREPARATION OF REINTEGRATION PROGRAMS IN THE ASPECT OF ENVIRONMENTAL SAFETY - Павленко, Олена; Марова, Світлана (SWorldJournal, 2022)
The state of the regulatory framework for environmental safety is analyzed. It is proved that the level of ecological danger is influenced by the state of natural, man-made, socio-political danger. It is determined that the territories of Donetsk and Luh